An integrated approach to the one-dimensional cutting stock problem in coronary stent manufacturing - Özdemir, Rifat Gürcan; AKTİN, AYŞE TÜLİN (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2009)
This paper presents a two-stage approach for pattern generation and cutting plan determination of the one-dimensional cutting stock problem. Calculation of the total number of patterns that will be cut and generation of the cutting patterns are performed in the first stage. On the other hand, the second stage determines the cutting plan. The proposed approach makes use of two separate integer linear programming models. One of these models is employed by the first stage to generate the cutting patterns through a heuristic procedure with the objective of minimizing trim loss. The cutting patterns obtained from Stage I are then fed into the second stage. In this stage, another integer linear programming model is solved to form a cutting plan. The objective of this model is to minimize a generalized total cost function consisting of material inputs, number of setups, labor hours and overdue time: subject to demand requirements, material availability, regular and overtime availability, and due date constraints. The study also demonstrates an implementation of the proposed approach in a coronary stent manufacturer. The case study focuses on the cutting phase of the manufacturing process followed by manual cleaning and quality control activities. The experiments show that the proposed approach is suitable to the conditions and requirements of the company. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: OR in health services; production; One-dimensional cutting stock problem; algorithm; lengths; number; üretim; tek boyutlu kesme stok sorunu; algoritma; uzunlukları; sayı